Development and Validation of Uv-Spectrometric Method for Quantitative Estimation of Trimetazidine and Ranolazine Combination of Drug in Tablet Dosage Form (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
A simple, accurate, precise and economical UV spectrophotometric method was developed and validated for the simultaneous estimation of trimetazidine (TMZ) and ranolazine (RAN) in combined tablet dosage forms used in treatment of chronic stable angina. Methanol was used as the solvent, and the absorbance was measured at 233 nm for TMZ and 271 nm for RAN. Beer-Lambert’s law was obeyed over the concentration range of 5-30μg/ml for TMZ and 10-60 g/ml for RAN with correlation coefficient (r²) of 0.9995 and 0.9997, respectively. The method was validated according to ICH Q2 (R1) guidelines for linearity, accuracy, precision, specificity, limit of detection (LOD), limit of quantification (LOQ), robustness, and ruggedness. The percentage recoveries ranged from 99.40-100.60% for TMZ and 99.30- 100.50% for RAN, confirming the accuracy of the method. The % RSD values for precision were 0.82% and 0.94%, respectively, indicating excellent reproducibility. The LOD and LOQ were 0.34μg/ml and 1.02μg/ml for TMZ, and 0.48μg/ml and 1.45μg/ml for RAN, respectively. Assay result of marketed tablet formulation were 99.85% for TMZ and 100.12% for RAN. The proposed method was found to be simple, sensitive, precise, and suitable for routine quality control analysis of trimetazidine and ranolazine in combined dosage forms.
Keywords: UV spectrophotometric method; trimetazidine (TMZ); ranolazine (RAN)